Faktor Pendukung dan Penghambat Operasional Kinerja Perangkat Desa Loru - Andi Nurfitria; Betty Betty; Adfiyani Fadjar (Jurnal Visi Manajemen, 2023)
The purpose of this activity is to find out the supporting and inhibiting factors for the operational performance of Loru Village Officials. This activity was carried out at the Loru Village office. The informant in this article is the village head of Loru. Methods of implementation using the method of observation, interviews and documentation. From the results of observing the factors that support the performance of Loru Village Officials, namely service orientation, integrity, commitment, discipline and cooperation. Meanwhile, the factors hindering the performance of Loru Village Officials are system, facility and infrastructure failures